The Effectiveness of Using Virtual Laboratories on Science Process Skills: A Systematic Literature Review - Nilawati Nilawati; Yasfi Ismayani; St. Hajar; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Applied Science and Technology, 2024)
The advancement of digital technology has encouraged the use of virtual laboratories as an alternative to practical experiments in science education. This study aims to examine the effectiveness of virtual laboratories on students' science process skills using a Systematic Literature Review (SLR) approach. The data were obtained from scientific articles published between 2015 and 2024, sourced from Google Scholar and Garuda, with a total of 20 articles meeting the selection criteria. The results indicate that virtual laboratories are effective in improving science process skills through interactive simulation-based experiments, as well as enhancing conceptual understanding and student engagement. Therefore, virtual laboratories can serve as an effective learning medium to support science practicum activities.